Perception, knowledge, and insights on the Brazilian consumers about nut beverages - Victor Jonas da Rocha Esperança; Isabelle Paes Leme de Castro; Thaisa Santos Marques; Otniel Freitas-Silva (International Journal of Food Properties)
“Plant-based beverages,” “plant-based milk” and “milk alternatives” are terms commonly used to refer to drinks made from plants, such as legumes, cereals, pseudocereals, and nuts. This study aimed to evaluate the perception and consumption of nut-based beverages by Brazilian consumers. An online questionnaire was prepared with socioeconomic and consumption questions and disseminated in digital media following established ethical standards. The almond beverage was the drink most consumed by the respondents and the Brazil nut beverage was the one that most aroused the most interest among the respondents. Nut beverages were elected as the healthiest, most sustainable, and nutritionally best beverages in comparison with soy beverages and cow’s milk. Fruits such as strawberries and bananas were cited as alternatives for flavoring these beverages. Consumers considered the possibility of fully and partially replacing cow’s milk and soy drinks with nut beverages. Interest in these along with plant-based milk was not restricted to the vegan segment, and these products were indicated as having strong potential for inclusion in the diets of omnivorous consumers. More studies on buying, purchase intention, acceptance, knowledge, and neophobia among Brazilian consumers are necessary for the development of these beverages, especially with more representative samples of society.